2021
DOI: 10.2174/1570163817666201229121033
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Role of Green Tea and its Main Constituent (Epigallocatechin-3-Gallate) in Pain Relief: A Mechanistic Review

Abstract: Medicinal plants and dietary supplements may provide an effective and safe treatment for pain relief. Green tea is one of the most common beverages with many several pharmacological activities. The results of various studies have indicated that green tea possesses antinociceptive effects. Many of the protective effects of green tea in the aspect of pain relief are attributed to its antioxidant and anti-inflammatory properties. Epigallocatechin ‐3‐gallate (EGCG) as one of the major phytochemical components in g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…KiOil ® is a patented combination of arnica, devil’s claw, green tea, and liposomes created by Medifarmagen SRL a Spin-off of Catanzaro’s University. These substances showed anti-inflammatory and analgesic properties, as described before [ 28 , 30 , 31 , 32 , 34 ].…”
Section: Methodsmentioning
confidence: 60%
See 1 more Smart Citation
“…KiOil ® is a patented combination of arnica, devil’s claw, green tea, and liposomes created by Medifarmagen SRL a Spin-off of Catanzaro’s University. These substances showed anti-inflammatory and analgesic properties, as described before [ 28 , 30 , 31 , 32 , 34 ].…”
Section: Methodsmentioning
confidence: 60%
“…Moreover, harpagoside inihibited lipopolysaccharide (LPS) induces the production of COX-2 and NO, acting on the nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) [ 33 ]. Green tea (one of the most popular drugs in the world) showed antioxidant, anti-inflammatory, and antinociceptive effects through the expression of molecules called catechins [ 34 ]. This substance showed efficacy in inflammatory pathologies including rheumatoid arthritis and osteoarthritis [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because chronic pain causes are poorly understood, and patients also suffer from comorbid conditions such as anxiety and depression, chronic pain remains poorly managed (Attal et al, 2011;Courtney et al, 2017;Markenson, 1996;Ossipov et al, 2014). Long-term use of analgesic drugs has its limitations, such as adverse effects and drug-to-drug interactions (Mercer Lindsay et al, 2021;Negah et al, 2021). Medicinal plants are a source of an infinite range of phytochemicals that have consistently been shown analgesic therapeutic properties (Forouzanfar et al, 2023;Negah et al, 2023;Rakhshandeh et al, 2021).…”
Section: Painmentioning
confidence: 99%
“…Long-term use of analgesic drugs has its limitations, such as adverse effects and drug-to-drug interactions (Mercer Lindsay et al, 2021;Negah et al, 2021). Medicinal plants are a source of an infinite range of phytochemicals that have consistently been shown analgesic therapeutic properties (Forouzanfar et al, 2023;Negah et al, 2023;Rakhshandeh et al, 2021). A critical evaluation of the clinical data regarding the adverse effects has shown that herbal remedies are generally better tolerated than synthetic medications (Izzo et al, 2016).…”
Section: Painmentioning
confidence: 99%
“…Epigallocatechin-3-gallate (EGCG), a major bioactive polyphenol in green tea, is known to suppress inflammation and oxidative stress [ 110 ]. Many studies have shown that EGCG has anti-inflammatory effects on chronic inflammatory diseases, such as neurodegenerative diseases and cancers, in a multifactorial manner [ 111 , 112 ].…”
Section: Phytochemicals Targeting the Jak–stat Pathwaymentioning
confidence: 99%